Cross-sectional and longitudinal analyses of the relative age effect in German youth football - Votteler, A.; Höner, O. (German Journal of Exercise and Sport Research, 2017)
Relative age effects (RAEs) describe an overrepresentation of youths born early within annual age cohorts. An understanding of how talent selection procedures cause RAE emergence in talent development programmes facilitates specific advice for their reduction. This cross-sectional and longitudinal study investigated the location of RAE differences between consecutive age categories and competition levels and RAE emergence through talent selection procedures. The sample comprised 35,390 male youth football players from the German talent development programme from three seasons (2010/2011-2012/2013). Cross-sectional analyses showed a consistent increase of RAEs over four ascending competition levels and slightly increasing RAEs from age categories U12 to U15, with a subsequent decrease until U19. The longitudinal analyses of talent selection procedures revealed an RAE increase for players newly selected for higher competition levels and no change in RAE extent for players retained across consecutive age categories at the same competition level. Findings were used to specify common suggestions to reduce RAEs in talent development programmes.